A Critical Overview of Systematic Reviews and Meta-Analyses of Acupuncture for Female Stress Urinary Incontinence. (17th May 2022) - Shi, Hongshuo; Zhao, Leizuo; Cui, Lirong; Wang, Zicheng; Wang, Dan; Liu, Pulin; Si, Guomin; Guo, Dong; Liu, Wenbin
Abstract : Objectives . As a urinary dysfunction disorder, stress urinary incontinence (SUI) is more common in women than in men. Acupuncture, a traditional minimally invasive technique, has potential efficacy in the treatment of SUI. The purpose of this overview is to critically assess the available evidence on acupuncture for the treatment of SUI in women. Methods . Two researchers searched seven databases for systematic reviews (SRs)/meta-analyses (MAs) of randomized controlled trials (RCTs) on acupuncture for SUI. Two researchers assessed the included SRs/MAs using the Assessment of Multiple Systematic Reviews 2 (AMSTAR-2), the Risk of Bias in Systematic (ROBIS) scale, the list of Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA), and the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system. Results . Eight published SRs/MAs were included in our overview. According to the results of the AMSTAR-2 assessment, all SRs/MAs were of very low quality. According to the ROBIS evaluation results, no SR/MA was assessed as low risk of bias. According to the results of the PRISMA checklist assessment, no SR/MA was fully reported on the checklist. According to GRADE, a total of 27 outcomes extracted from the included SRs/MAs were evaluated, and only 1 was rated as high quality. Conclusions . Acupuncture may be an effective and safe complementary treatment for SUI in women. However, further standard and comprehensive SRs/MAs and RCTs are needed to provide an evidence-based medical rationale for this.